2023
DOI: 10.3390/su15075979
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Ocean Management (IOM) for Marine Sustainable Development Goal (SDG)14: A Case Study of China’s Bohai Sea

Abstract: Marine development and eco-environmental management have received increasing attention over the past two decades, however, no effective universal approach has been established to achieve marine development without destroying marine ecosystems. This study discusses the integrated ocean management (IOM) for meeting the sustainable development goal (SDG14) through the following four aspects: the marine eco-environment foundation, market mechanism, management support, and space consideration. Our findings highligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
0
0
Order By: Relevance
“…Until the ecological civilization was proposed around 2012, the management of the Bohai Sea gradually moved towards the coupling and collaborative development of various subsystems and the ILSM. It has been recognized that the management of the Bohai Sea is inseparable from development and resource and environmental issues (Xue et al, 2023), i.e., resource exploitation, ecological and environmental issues, and socioeconomic development and are interrelated and mutually restricted. Therefore, the management of Bohai Sea is bound to be a process of coupling and coordination, and the isolated emphasis on the development of an individual system cannot achieve sustainable development.…”
Section: Methods and Materials 21 Conceptual Framework Of The Coordin...mentioning
confidence: 99%
See 3 more Smart Citations
“…Until the ecological civilization was proposed around 2012, the management of the Bohai Sea gradually moved towards the coupling and collaborative development of various subsystems and the ILSM. It has been recognized that the management of the Bohai Sea is inseparable from development and resource and environmental issues (Xue et al, 2023), i.e., resource exploitation, ecological and environmental issues, and socioeconomic development and are interrelated and mutually restricted. Therefore, the management of Bohai Sea is bound to be a process of coupling and coordination, and the isolated emphasis on the development of an individual system cannot achieve sustainable development.…”
Section: Methods and Materials 21 Conceptual Framework Of The Coordin...mentioning
confidence: 99%
“…Not only has the functional departments been integrated, but the leadership system has also been reformed, and the ecological environment department is no longer under the management of the local government, but directly under the central government . Currently, it has become a vertical leading organization from the MEE, forming the Ecological and Environmental Protection Bureau at the provincial, the municipal, and then the county-level (Xue et al, 2023). With respect to the resource development and management bureaus system, the ILSM system has been combined with the Ministry of Natural Resources/department/bureau, with cooperation from the fisheries, water conservation, shipping, and other departments.…”
Section: Introduction Of the Study Areamentioning
confidence: 99%
See 2 more Smart Citations
“…demonstrated that the transaction system for sea use rights operates as a hierarchical framework within the boundaries of state ownership and the requirement for payment for sea usage and the functioning of the SUR transaction system depend on a combination of government and market mechanisms [20]. Xue et al (2023) examined the use of IOM to achieve the sustainable development aim by focusing on the marine eco-environment foundation, market mechanism, management support, and space consideration [21]. investigated ways to enhance the productivity of the marine sector and promote the high-quality development of the marine economy through financial support using the framework of Integrated Land-Sea Management [22].…”
Section: Research On the Right To Use Sea Areasmentioning
confidence: 99%